Entre o machado e o punhal: configurações da violência em Tutaméia (Terceiras Estórias) de João Guimarães Rosa - Sarah Maria Forte Diogo (2015)
This thesis is focused on 'Tutaméia (Terceiras Histórias)' , by João Guimarães Rosa, in order to analyze the configurations of violence in 'Antiperipléia', 'Arroio-das-Antas', 'A vela ao Diabo', 'Azo de almirante', 'Barra da vaca', 'Como ataca a sucuri', 'Curtamão', 'Desenredo', 'Droenha', 'Esses Lopes', 'História nº 3', 'Estoriinha', 'Intruge-se', 'No prosseguir', 'Quadrinho de estória', 'Sinha Secada' and '-Uai, eu?'. To do so, the research has examined the part of the author's critical fortune, seeking to approach construction of the work with four prefaces and the considerations that Rosa does about paradoxes, for example. It was also analyzed the opposition proposed by the writer between story and history and the possibility of understanding the narratives as 'counter-narratives'. The choice of stories is justified by the presence of explicit or implicit pictures of violence. We assume that these seventeen narratives, of forty that constitute the work, violence functions as a structural topic of the text. From this topic, the other stories are, also, organized. Besides that, we observed that, in all 'Tutaméia''s stories, the linguistic violence is presente, with the proposition of a 'becoming' in the language, a language that forces and tenses the thought. What interested us was the existence, next to this violence, of the other violences - the social violences - materialized on the paths adopted. As results, we noticed that the presente violences set free, but imprison and the only carachters who escape from that are the ones who decide not to violate the others.